2021
DOI: 10.3390/healthcare9111517
|View full text |Cite
|
Sign up to set email alerts
|

Digital Health Platforms in Saudi Arabia: Determinants from the COVID-19 Pandemic Experience

Abstract: COVID-19 poses a significant burden to healthcare systems. Healthcare organisations with better health innovation infrastructures have faced a reduced burden and achieved success in curbing COVID-19. In Saudi Arabia, digital technologies have played a vital role in fighting SARS-CoV-2 transmission. In this paper, we aimed to summarise the experience of optimising digital health technologies in Saudi Arabia as well as to discuss capabilities and opportunities during and beyond the COVID-19 pandemic. A literatur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 35 publications
1
33
0
Order By: Relevance
“…Moreover, this is the first study to fully integrate PMT, the extended TAM, and the SUS. The significant and substantial findings can be used as a theoretical foundation, particularly in designing a new mobile application for disease-control tracking worldwide [ 57 , 58 , 59 , 60 , 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this is the first study to fully integrate PMT, the extended TAM, and the SUS. The significant and substantial findings can be used as a theoretical foundation, particularly in designing a new mobile application for disease-control tracking worldwide [ 57 , 58 , 59 , 60 , 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, some authors have reported that the transition to electronic services in the Saudi health system was very slow ( 17 , 26 ). However, since the COVID-19 pandemic, the Saudi health system has witnessed a significant boost in digitalizing health services ( 15 ). Thus, it was crucial to identify the factors that influence actual use and intention to use such services.…”
Section: Discussionmentioning
confidence: 99%
“…This is also in line with the Ministry of Health 2030 vision and a new model of care in Saudi Arabia, where adapting technology in the delivery of care is one of the central goals to improve the quality and accessibility of care to the whole population (14). Several studies have been conducted to assess digital health in Saudi Arabia; however, these studies have focused on one e-service (phone calls) or certain health services (dermatology) or were conducted before the COVID-19 pandemic (15)(16)(17). This study adds to the literature by identifying the factors influencing actual use and intention to use e-consultations during and after the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…At the population level, public authorities and governments introduced lockdowns and quarantine to prevent the spread of the virus [ 4 ], since it was discovered that the virus is more active in social areas. The quarantine, stay-at-home, and social distancing policies were implemented to control the spread of the infection [ 4 , 5 ]. Research indicates that many healthcare systems were vulnerable in the face of such a pandemic, as it has increased existing challenges such as staff shortages, personal protective equipment (PPE) shortages, and intensive care unit (ICU) and hospital bed capacities [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The quarantine, stay-at-home, and social distancing policies were implemented to control the spread of the infection [ 4 , 5 ]. Research indicates that many healthcare systems were vulnerable in the face of such a pandemic, as it has increased existing challenges such as staff shortages, personal protective equipment (PPE) shortages, and intensive care unit (ICU) and hospital bed capacities [ 5 , 6 , 7 ]. This extraordinary situation imposes extra challenges on the existing healthcare systems.…”
Section: Introductionmentioning
confidence: 99%